Household Air Pollution Exposure and Influence of Lifestyle on Respiratory Health and Lung Function in Belizean Adults and Children: A Field Study - Kurti, Stephanie P.; Kurti, A. N.; Emerson, Sam R.; Rosenkranz, Richard R.; Smith, Joshua R.; Harms, Craig A.; Rosenkranz, Sara K. (My University, 2016)
Household air pollution (HAP) contributes to the global burden of disease. Our primary purpose was to determine whether HAP exposure was associated with reduced lung function and respiratory and non-respiratory symptoms in Belizean adults and children. Our secondary purpose was to investigate whether lifestyle (physical activity (PA) and fruit and vegetable consumption (FV)) is associated with reported symptoms. Belizean adults (n = 67, 19 Male) and children (n = 23, 6 Male) from San Ignacio Belize and surrounding areas participated in this cross-sectional study. Data collection took place at free walk-in clinics. Investigators performed initial screenings and administered questionnaires on (1) sources of HAP exposure; (2) reported respiratory and non-respiratory symptoms and (3) validated lifestyle questionnaires. Participants then performed pulmonary function tests (PFTs) and exhaled breath carbon monoxide (CO). There were no significant associations between HAP exposure and pulmonary function in adults. Increased exhaled CO was associated with a significantly lower forced expiratory volume in 1-s divided by forced vital capacity (FEV1/FVC) in children. Exposed adults experienced headaches, burning eyes, wheezing and phlegm production more frequently than unexposed adults. Adults who met PA guidelines were less likely to experience tightness and pressure in the chest compared to those not meeting guidelines. In conclusion, adults exposed to HAP experienced greater respiratory and non-respiratory symptoms, which may be attenuated by lifestyle modifications.
Citation: Kurti, S. P., Kurti, A. N., Emerson, S. R., Rosenkranz, R. R., Smith, J. R., Harms, C. A., & Rosenkranz, S. K. (2016). Household Air Pollution Exposure and Influence of Lifestyle on Respiratory Health and Lung Function in Belizean Adults and Children: A Field Study. International Journal of Environmental Research and Public Health, 13(7), 12. doi:10.3390/ijerph13070643
Keywords: Pulmonary Function; Lifestyle; Physical Activity; Indoor Air Pollution; Household Air; Respiratory Physiology